Socioeconomic effects of Oyo state government COVID-19 palliatives on tomato smallholder farmers - Ayedun, B.; Akande, A. (Universe Publishing Group - UniversePG, 2023)
This study interviewed 197 farmers that benefitted from the government palliative in the form of tomato farm inputs to help farmers contain the negative effects of COVID-19 of hunger, food insecurity, and poverty. Demographic features show that the average family size was 6, average age of the beneficiaries was 43, gender of the household heads shows that the beneficiaries have 67% males and 33% females. Production features show that 28% of the tomato farmers intercropped their tomato with other crops, 40% of them went through government training, and 25% of them accessed credit to take of their farms. Farmer to farmer was the main source of information (77%). Using the Likert Scale characterization shows that 74.6% of the farmers believed that the palliative increased their yield, 81.2% agreed that the palliatives just reduced hunger in their household, while 86.3% agreed that there was an increase in their farm income as a result of the intervention. Logit regression results reveal that Farmer’s Age, Farm Income, Loan Access, and Tomato Yield are the factors that significantly increased perception of tomato farmers on hunger reduction. Farm Income and Loan Access factors have a positive coefficient which is significant at the 1% level, while Farmer’s Age and Tomato Yield have positive coefficients but is significant at the 5% level. Association Membership negatively and significantly reduced farmers’ perception of hunger reduction at the 5% level of probability while farmer-to-farmer information sources significantly reduced it at a 1% level of probability; meaning that only government extension agents and the media positively influenced information transfer on the government palliative efforts. The study recommends that government assistance should be extended to other resource-poor farmers and that getting access to loans should be made easier for farmers by the government.